Resilience of Local Artists in the Kecak Ramayana Performance at Uluwatu, Bali as a Sacred Negotiation Amidst Tourism Commodification - Robby Hidajat; Pujiyanto Pujiyanto; Surasak Jamnongsarn (Mahesa Research Center, 2026)
This study examines the resilience of local artists involved in the Kecak Ramayana performance at Uluwatu, Bali, particularly in negotiating sacred cultural values with the demands of tourism commodification. The study employs an interdisciplinary qualitative approach that integrates perspectives from performing arts, ethnomusicology, and visual communication design. Data were collected through direct observation of Kecak Ramayana performances, audiovisual documentation, and in-depth interviews with local artists and cultural practitioners. The analysis focused on three dimensions of performance: movement structure and dramaturgy, vocal rhythm as a spiritual element, and visual narratives and symbolism. The findings indicate that local artists are not passive recipients of tourism commodification but active cultural agents who selectively adapt performance elements while maintaining core ritual, spiritual, and philosophical values. Adjustments in performance duration, narrative presentation, staging, lighting, and visual communication are made to accommodate tourist audiences, whereas fundamental movement patterns, vocal practices, and spiritual values are retained. This process demonstrates that tourism commodification can become a space for cultural negotiation and adaptive resilience rather than necessarily resulting in cultural degradation. The study concludes that community-centered artistic production enables local artists to maintain cultural identity while simultaneously responding to economic and communicative demands within the tourism industry. Thus, the resilience of Kecak Ramayana artists is reflected in their ability to transform and contextualize traditional performance without abandoning its cultural and spiritual foundations.